Christian Wolff Wade in the Water, Kammer Klang, Café Oto, London. (28th September 2016) - Fox, Christopher
Abstract : Is there any London concert venue more suited to the music of Christian Wolff than Café Oto? It's not so much its status as the nexus of hipster lounge and ascetic experimentalism as its noisiness. No sooner had violinist Aisha Orazbayeva and pianist Joseph Houston begun to play Wolff's indeterminate classic For 1, 2 or 3 People (1964) than I was reminded of John Cage:One day when the windows were open, Christian Wolff played one of his pieces at the piano. Sounds of traffic, boat horns … were more easily heard than the piano sounds themselves. Afterward, someone asked Christian Wolff to play the piece again with the windows closed. Christian Wolff said … it wasn't really necessary, since the sounds of the environment were in no sense an interruption of those of the music.